"Contra omnes et singulos a via domini aberrantes": accounting for confession and pastoral power during the Roman Inquisition (1550–1572). Issue 4 (23rd February 2021) - Bigoni, Michele; Antonelli, Valerio; Funnell, Warwick; Cafaro, Emanuela Mattia
Abstract : Purpose: The study investigates the use of accounting information in the form of a confession as a tool for telling the truth about oneself and reinforcing power relations in the context of the Roman Inquisition. Design/methodology/approach: The study adopts Foucault's understanding of pastoral power, confession and truth-telling to analyse the accounting practices of the Tribunal of the Inquisition in the 16th century Dukedom of Ferrara. Findings: Detailed accounting books were not simply a means for pursuing an efficient use of resources, but a tool to force the Inquisitor to open his conscience and provide an account of his actions to his superiors. Accounting practices were an identifying and subjectifying practice which helped the Inquisitor to shape his Christian identity and internalise self-discipline. This in turn reinforced the centralisation of the power of the Church at a time of great crisis. Research limitations/implications: The use of accounting for forcing individuals to tell the truth about themselves can inform investigations into the use of accounting records as confessional tools in different contexts, especially when a religious institution seeks to reinforce its power. Social implications: The study documents the important but less discernible contributions of accounting to the formation of Western subjectivity at a time which Foucault considers critical in the development of modern governmental practices. Originality/value: The study considers a critical but unexplored episode in Western religious history. It offers an investigation of the macro impact of religion on accounting practices. It also adds to the literature recognising the confessional properties of written information by explicitly focusing on the use of financial information as a form of confession that has profound power implications.